Pharmacological treatment of postoperative recurrence of Crohn's disease: Protocol for systematic review and network meta-analysis. - Tianxiang Jiang; Zhaolun Cai; Chunjuan Liu; Bo Zhang (PLoS ONE)
Background Crohn's disease (CD) is a chronic inflammatory condition primarily affecting the digestive system. When dealing with complex cases like intestinal blockages or perforations, surgery becomes the primary treatment option. However, surgery doesn't offer a complete cure, and the possibility of recurrence remains. To manage CD recurrence after surgery, various treatment choices are available, including steroids, monoclonal antibodies, immunomodulators, and further surgery. Regrettably, the current body of evidence doesn't definitively establish which of these treatments is the most effective and safe. Thus, our research aims to provide insights into the Validity and security of different treatment approaches for managing CD recurrence after surgery. Methods Search of EMBASE, PubMed, Web of Science Core Collection and the Cochrane Central Register of Controlled Trials will be conducted to include researches that examine the validity of treatments for recurrent CD after surgery. Our analysis will distinguish between two types of studies: randomized controlled trials (RCTs) and non-randomized studies with at least two different treatments, each evaluated separately. We will employ Bayesian network meta-analyses to systematically compare the effectiveness and safety of these treatments. Additionally, subgroup analyses will be performed according to recurrence status and postoperative prophylactic medication. To clarify the variation of studies, sensitivity analyses will be performed. And we may use meta-regression as an additional approach if relevant data are available. We will also rigorously access the certainty of evidence using the Grading of Recommendations, Assessment, Development, and Evaluation framework. Discussion This analysis will provide a comprehensive assessment of the latest evidence on available treatments for patients with postoperative recurrence of CD, which will provide recommendations for clinical practice. Trial registration Systematic review registration INPLASY2023110021. (DOI: 10.37766/inplasy2023.11.0021).